Assessment of respiratory function and aerobic capacity in postmenopausal women participating in water aerobics classes - Sobczak, Katarzyna; Wochna, Krystian; Pietrusik, Krzysztof; Strzelczyk, Ryszard (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Respiratory function is subject to the aging process, similarly to that of multiple other systems. Regular aquatic exercise favors physical development, and improves circulation and respiration, as well as overall health. Aim of Study. The purpose of the study was to assess the impact of a 12-week training program involving water aerobics on respiratory system function and aerobic capacity in post-menopausal women. Material and Methods. The study included 30 women (21 in the study group, 9 controls). Women in the study group participated in supervised water aerobics classes, twice a week for 3 months. At the beginning and end of the study, all the women underwent a spirometry test and an exercise test by an ergometer. Results. An analysis of changes after the training program demonstrated a significant increase of the maximal aerobic capacity in the study group (p < 0.05). No significant changes were found in spirometry indicators (VC) or airflow parameters in the large and small airways (MEF75, MEF50) following a 12-week water aerobics program. Conclusions. The implemented training program for healthy postmenopausal women did not improve the spirometry indicators studied, and the observed aerobic capacity increase likely resulted from improved circulatory and metabolic performance that determines an individual’s exercise tolerance and health.
Keywords: spirometry; postmenopausal women; maximum oxygen uptake